Energy Access and Energy Security in Asia and the Pacific - Benjamin Sovacool (Asian Development Bank (ADB), 2013)
Lack of access to electricity and modern cooking fuels constitutes energy poverty. Access to modern energy requires improved technologies and financing instruments and sources. The pro-poor public–private partnership model is one useful vehicle for raising capital to finance projects. Five factors appear to be necessary in combination for programs and partnerships to successfully promote energy access and eradicate energy poverty: selecting appropriate technology, promoting community participation, emphasizing maintenance and service, coupling service with incomes, and building local capacity.
hdl:11540/2058
Keywords: K32; L38; N75; 330; energy access; energy and development; energy poverty; indoor air pollution